Multimodalitas sebagai Perspektif Baru Pembelajaran Pragmatik Edukasional: Persepsi Urgensi Inklusinya (Multimodality as a New Perspective of Educational Pragmatic Learning: Perception of the Urgency of Inclusion) - R. Kunjana Rahardi (Jurusan Tadris Bahasa Indonesia, 2022)
The purpose of this study was to describe the perception of the urgency of the components of socio-semiotic multimodality to be included in educational pragmatic learning. The theory that underlies this research is the social semiotic theory of M.A.K. Halliday. Data in the form of perceptions of aspects of social-semiotic multimodality were collected through a questionnaire. The collected data are identified, classified, and typified. The results showed that students' understanding of multimodality in the design of multimodality-based educational pragmatic learning models: was 72%, the existence of modality linguistic aspects at 52%, the inclusion of visual aspects at 68%, aural aspects in determining speech intent at 100%, the inclusion of sound aspects in determining speech intent 48 %, inclusion of gestural aspects 56%, spatial aspects required in the design of learning models 100%.Â Tujuan penelitian ini adalah untuk mendeskripsikan persepsi urgensi komponen-komponen multimodalitas sosial-semiotik dimasukkan dalam pembelajaran pragmatik edukasional. Teori yang mendasari penelitian ini adalah teori semiotika sosial M.A.K. Halliday. Data berupa persepsi aspek-aspek multimodalitas sosial-semiotik yang dikumpulkan melalui kuesioner. Data yang terkumpul diidentifikasi, diklasifikasi, dan ditipifikasi. Hasil penelitian menunjukkan bahwa pemahaman mahasiswa ihwal multimodalitas dalam desain model pembelajaran pragmatik edukasional berbasis multimodalitas: 72%, eksistensi aspek linguistik modalitas 52%, inklusi aspek visual 68%, aspek aural dalam penentuan maksud tuturan 100%, inklusi aspek suara dalam penentuan maksud tuturan 48%, inklusi aspek gestural 56%, aspek spasial diperlukan dalam desain model pembelajaran 100%